Greek students’ attitudes toward rape - Gari, Aikaterini; Georgouleas, George; Giotsa, Artemis; Stathopoulou, Eleni Anna (Psychology: the Journal of the Hellenic Psychological Society, 2020)
Literature on sexual harassment and violence against women describes a variety of myths and stereotypes regarding partial or total responsibility of rape victims and their “enjoyment” of sexual violence. Rape stigma and rape myths are aspects of generalized attitudes toward victims of rape and rapists, while it seems that sexual violence remains a taboo in today’s western societies. This study explores Greek university students’ attitudes towards rape. A questionnaire created for the purpose of this study was administered to 950 Greek students at the University of Athens and at the University of Ioannina, divided into three groups: a group of students from the Faculty of Law, a group from Departments orientated to Humanistic and Social Sciences and a group of students from other Faculties and Departments of Applied Sciences. Factor analysis revealed four factors: “Rape victim’s responsibility”, “Defining the concept of rape”, “Rape motivation” and “Rapist’s characteristics”. In line with previous research findings, the results indicated that women were less accepting of conservative attitudes towards rape than men; they also seemed to reject attitudes of “blaming the victim” more, and to hold negative views of rapists. Additionally, the results showed that students of rural origin retain more conservative attitudes with respect to the victim’s responsibility and the rapist’s characteristics than students of urban origin. Finally, students in Law Departments seemed to have accepted more moderate attitudes than the other two groups of students; they mostly disagree with conservative attitudes regarding victim’s responsibilities along with the Social Science students, but they agree more with Applied Sciences students in defining rape.